Integrated microbiomics and metabolomics analysis reveals distinct profiles in carbapenem-resistant Acinetobacter baumannii and Escherichia coli infections in Pancreatitis-associated sepsis - Kongfan Zhu; Hua Hu; Zhijian Yang; Zhongchao Zhu (PLoS ONE, 2026)
Background Pancreatitis-associated sepsis (PAS) caused by carbapenem-resistant bacteria poses significant clinical challenges. The objective of this research was to examine the microbial and metabolic profiles of individuals with carbapenem-resistant Acinetobacter baumannii (CRAB) and Escherichia coli (CREC) infections using integrated microbiomics and metabolomics approaches. Methods Peripheral blood samples from 11 PAS patients (8 CRAB, 3 CREC) were analyzed using 16S rDNA gene sequencing and untargeted metabolomics via LC-MS. Microbial diversity, community structure, and differential metabolites were examined between CRAB and CREC groups. Results CRAB patients exhibited higher microbial diversity compared to CREC patients. p- Proteobacteria , p- Firmicutes , and p- Cyanobacteria predominated in both patient groups. Significant differences in microbial composition were observed, with p- Proteobacteria more abundant in CRAB and p- Cyanobacteria in CREC samples. g- Enhydrobacter and s- Moraxella osloensis were the biomarkers, significantly higher in CREC patients. Metabolomic analysis revealed 328 differential metabolites between groups, with the majority being downregulated in CRAB. The main categories of identified differential metabolites were amino acids and their derivatives. These differential metabolites were closely related to various metabolic pathways. The most significant metabolic difference between the two patient groups was the level of triglycerides. R-2 Methanandamide and 13-(β-D-glucosyloxy) docosanoic acid showed the highest correlation with g- Enhydrobacter and s- Moraxella osloensis . Conclusion In PAS patients, s- Moraxella osloensis is a biomarker distinguishing CRAB and CREC infections, correlating with R-2 Methanandamide and 13-(β-D-glucosyloxy) docosanoic acid.